The liturgy in medieval England : a history - Pfaff, Richard William, 1936-2016. (Cambridge ; New York : Cambridge University Press, 2009)
"This is the first comprehensive historical treatment of the Latin liturgy in medieval England. Richard Pfaff constructs a history of the worship carried out in churches - cathedral, monastic, or parish - primarily through the surviving manuscripts of service books, and sets this within the context of the wider political, ecclesiastical, and cultural history of the period. The main focus is on the mass and daily office, treated both chronologically and by type, the liturgies of each religious order and each secular 'use' being studied individually. Furthermore, hagiographical and historiographical themes - respectively, which saints are prominent in a given witness and how the labors of scholars over the last century and a half have both furthered and, in some cases, impeded our understandings - are explored throughout. The book thus provides both a narrative account and a reference tool of permanent value."--Jacket.
Introduction -- Early Anglo-Saxon England: a partly traceable story -- Later Anglo-Saxon: liturgy for England -- The Norman Conquest: cross fertilizations -- Monastic liturgy, 1100-1215 -- Benedictine liturgy after1215 -- Other monastic orders -- The non-monastic religious orders: canons regular -- The non-monastic religious orders: friars -- Old Sarum: the beginnings of Sarum Use -- New Sarum and the spread of Sarum Use -- Exeter: the fullness of secular liturgy -- Southern England: final Sarum Use -- Regional Uses and local variety -- Towards the end of the story.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 050
Keywords: Catholic Church -- England -- Liturgy -- History -- To 1500.; Catholic Church; Liturgics; Liturgical language -- Latin; England -- Church history -- 1066-1485.; RELIGION -- Institutions & Organizations; RELIGION -- Christian Rituals & Practice -- Worship & Liturgy; Liturgical language -- Latin; Liturgics; England; Liturgie; England; To 1500; Electronic books; Church history; History